2016
DOI: 10.1111/ijcp.12853
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of the contrast, radiation dose and image quality of contrast-enhanced CT scans of paediatric abdomens using a low-concentration iodinated contrast agent and low tube voltage combined with 70% ASIR algorithm

Abstract: The scanning protocol using a low tube voltage (80 kVp) together with 70% ASIR and a low-concentration iodinated contrast agent (270 mg I/mL) enables a 37% reduction in iodine load and a 30% reduction in radiation dose while maintaining compatible image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As mentioned previously, the recommendations regarding CA application protocols in this patient population are heterogeneous, but 2 ml/kg body weight CA volume is commonly advised 1517,2634 . Literature data also suggest several alternatives regarding contrast injection protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, the recommendations regarding CA application protocols in this patient population are heterogeneous, but 2 ml/kg body weight CA volume is commonly advised 1517,2634 . Literature data also suggest several alternatives regarding contrast injection protocols.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative option to reduce side effects is the usage of low-concentrated iodinated CA (e.g. 270 mgI/ml) 21,33,34 . However, this concentration is still considerably higher than those used in MBT (CA dilution to 100 mg Iodine/ml).…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in adoption of scanners with ATVS and dual-energy CT capability, more studies are being performed with low kVp/low keV, and, at our practice, more than 80% of oncologic abdominopelvic CT studies are performed with these techniques. These techniques have attracted an interest in modifying intravenous contrast media protocols, and independent investigations have reported the feasibility of reducing intravenous iodine dose by up to 70% for abdominal CT or CT angiography (10)(11)(12)28). However, there is also a need to modify existing OCM protocols.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have demonstrated that the low voltage and adaptive statistical iterative reconstruction algorithm could reduce the radiation dose and contrast agent dosage in abdominal angiography; however, the conditions were applied only in pediatric patients and lower weight population ( 18 19 ). After studying the relationship between tube voltage and CT attenuation value of iodine, Huda et al ( 20 ) confirmed that the attenuation value of iodinated enhancement increased at a lower tube voltage, leading to higher enhancement.…”
Section: Discussionmentioning
confidence: 99%